KEAKTIFAN DAN HASIL BELAJAR SISWA PADA MATERI TERMODINAMIKA MELALUI PENERAPAN PROBLEM BASED LEARNING BERBANTUAN GOOGLE SITES - Cinta Aurelia Sinaga; Juniastel Rajagukguk (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of the google sites-assisted Problem-Based Learning (PBL) model on students’ learning activities and learning outcomes in thermodynamics in Grade 11 at SMA Negeri 1 Percut Sei Tuan. The research design used was a quasi-experimental study with a pretest-posttest control group design. The research sample consisted of two classes selected using simple random sampling: the experimental class (XI Matlangraf, n=30), which implemented the google sites-assisted problem based learning model, and the control class (XI Matlangko-3, n=30), which followed conventional instruction. Learning activity data were collected through observation sheets over three sessions, while learning outcome data were obtained from a multiple-choice test instrument (17 items) that measured cognitive abilities at levels C4–C6. Data analysis utilized the normality test (Shapiro-Wilk), homogeneity test (Levene), and t-test using SPSS 25.0. The correlation between learning activities and learning outcomes was analyzed using Pearson’s correlation. The results of the study indicate that: (1) the average learning activity in the experimental class increased consistently from 61.83 (moderately active) in the first session to 85.00 (active) in the third session, with an overall average of 72.83 (active); (2) the average learning outcomes of the experimental class (83.83) were significantly higher than those of the control class (71.50) based on a one-tailed t-test (t=6.257; Sig.=0.000<0.05); and (3) there is a significant positive relationship between learning activity and student learning outcomes (r=0.597; p<0.05). Thus, the implementation of the google sites-assisted problem based learnig model has proven effective in improving student learning activity and outcomes in thermodynamics.